2009
DOI: 10.1007/s00421-009-1337-6
|View full text |Cite
|
Sign up to set email alerts
|

Elderly oarsmen have larger trunk and thigh muscles and greater strength than age-matched untrained men

Abstract: To evaluate whether regularly performed rowing exercise affects the trunk muscles size and function, and to examine the effect of rowing exercise on thigh muscle size and function in elderly rowers, we compared the cross-sectional area (CSA) and strength of these muscles in elderly male rowers and in age-matched untrained men. Participants were 16 elderly rowing-trained men (ROW age, 67.8 +/- 2.3 years) and 18 elderly untrained men (CON 66.2 +/- 3.0 years). CSA was measured by MRI in the trunk and thigh muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 28 publications
3
25
1
Order By: Relevance
“…Thus, rowing is recognized as a useful resistance exercise for increasing muscle mass. 25.3 ) (Asaka et al 2010 ). In the DXA study, we demonstrated that arm, leg, and trunk lean soft tissue mass were signifi cantly higher in elderly rowers than in elderly untrained controls and bone mineral density was also signifi cantly higher in senior rowers than in senior sedentary controls (Sanada et al 2009 ).…”
Section: Rowing As a Resistance Exercisementioning
confidence: 86%
See 1 more Smart Citation
“…Thus, rowing is recognized as a useful resistance exercise for increasing muscle mass. 25.3 ) (Asaka et al 2010 ). In the DXA study, we demonstrated that arm, leg, and trunk lean soft tissue mass were signifi cantly higher in elderly rowers than in elderly untrained controls and bone mineral density was also signifi cantly higher in senior rowers than in senior sedentary controls (Sanada et al 2009 ).…”
Section: Rowing As a Resistance Exercisementioning
confidence: 86%
“…During rowing exercise, the trunk motion accounts for 50 % of the total rowing power and the leg motion counts for 40 % (Tachibana et al 2007 ). Recently, we examined the body composition of elderly rowers assessed by dualenergy X-ray absorption (DXA) and magnetic resonance imaging (MRI) (Asaka et al 2010 ;Sanada et al 2009 ;Yoshiga et al 2002b ). It is critically important for elderly people to prevent trunk and leg muscle wasting.…”
Section: Rowing As a Resistance Exercisementioning
confidence: 99%
“…Rowing is a type of activity which involves resistance exercises [26] that engage the muscles of the upper and lower limbs and the trunk. Asaka et al [27] also recognised rowing as an exercise that increases skeletal muscle size. In a study performed in elderly oarsmen, the authors demonstrated that rowing is a favourable training modality for benefiting the thigh and trunk muscles, especially for the psoas major.…”
Section: Discussionmentioning
confidence: 97%
“…These parameters of muscle morphology are also often investigated to identify expected age-related muscle changes (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…These parameters of muscle morphology are also often investigated to identify expected age-related muscle changes (13,14).Many, though not all, studies analysing spinal muscle CSA and MFI report intra-and/or inter-rater reliability as part of their investigations (4,5,7,15,16), many of which demonstrate strong intra-rater reliability of lumbar erector spinae and multifidus CSA, with an intraclass correlation (ICC) ranging from 0.85 (5, 15) to 0.98 (4) and an inter-rater reliability ranging from 0.77 (7) to 0.85 (5). However, the specific reporting of intra-and/or inter-rater reliability findings is often lacking regarding the description of the methodology of assessor agreement and assessor experience.…”
mentioning
confidence: 99%